PENGEMBANGAN OBJEK WISATA TAMAN KULINER PACIRAN OLEH BADAN USAHA MILIK DESA (BUMDesa) AMANAH BERSAMA DI DESA PACIRAN KECAMATAN PACIRAN KABUPATEN LAMONGAN - Husnul Chitam; Agus Widiyarta (Universitas Bina Taruna Gorontalo, 2023)
The purpose of this study is to find out, analyze and describe the Development of Paciran Culinary Park Tourism Objects by Business Entities Owned by Amanah Bersama Village in Paciran Village, Paciran District, Lamongan Regency by using four focuses in accordance with the theory of developing tourist destinations according to Sedarmayanti (2018), namely tourist attractions, attractions, facilities, and accessibility. This research uses qualitative descriptive research methods with data collection techniques in the form of interviews, observations, and documentation. The data sources used are informants and documents related to the research. The results of the study showed that the development of paciran culinary park tourist attractions was good, because it was in accordance with the focus of developing tourist destinations, namely: the existence of natural and artificial tourist attractions, the existence of attractions organized, the existence of tourist facilities and public facilities available, and the ease of accessibility to tourist attractions. The conclusion of this study is that it is in accordance with the development of paciran culinary park tourist attractions with the theory that is a reference in the development of tourist destinations.